Effects of The Shell Thickness On The Directional Deformation And Buckling On The Cylindrical Steel Water Tanks Under The Kobe Earthquake Loading - Ahmet Celal Apay; Ali İhsan Çelik; Mehmet Metin Köse; Tahir Akgül (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Cylindrical steel storage tanks are widely used for the storage of various liquids, industrial chemicals and firefighting waters. They have been used for cooling purposes in nuclear power plants in recent years. Liquid-storage tanks have many different configurations; however, in this study, cylindrical ground-supported liquid steel tanks were preferred because of their simplicity in design and construction as well as their efficiency in resisting hydrostatic and hydrodynamic applied loads, when compared with other configurations. If liquid steel tanks are damaged in an earthquake, they can also cause great financial and environmental damage with their hazardous chemical contents. These tanks may be exposed to some damages such as elephant-foot buckling, diamond-shape buckling, overturning and uplifting during earthquakes. Dimensions of cylindrical open-top, flat-closed and torispherical-closed top tanks were determined for 3D-finite element method (FEM) models in an ANSYS workbench software. This article focuses on the seismic-activity-resistant ground-supported cylindrical (vertical) steel storage liquid tanks. Seismic analyses were conducted under Kobe earthquake loads. The frequency values calculated with API 650 were verified with the FEM model results. Directional deformation, buckling results were presented for both impulsive and convective regions. According to API 650 standard, the tank shell thickness is 6 mm. Simulations were performed with 4 mm and 8 mm shell thickness for tanks. In this study, directional deformation and buckling were observed with simulations made by choosing the shell thickness under (4 mm) the standard and above (8 mm) the standard, unlike the approaches in the literature. As a result, it was observed that the 8 mm shell thickness determined above the standard increased the deformation in the flat-closed tank. In addition, torispherical dome-shaped tanks have been observed to lower directional deformation and buckling in any case. The differences obtained are detailed with